EVALUASI PEMANFAATAN MEDIA DIGITAL DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (STUDI LITERATUR) - Luthfia Chairunnisa; Gita Belita; Muhammad Fahriza Lubis; Abdul Rahman (Islamic Education Department, Islamic University of Majapahit (Universitas Islam Majapahit) Mojokerto, Indonesia, 2026)
The use of digital media in Islamic Religious Education (PAI) learning is a strategic effort to improve the quality of learning in the digital era. Digital media allows for a more varied, interactive, and contextual presentation of PAI material, thus adapting to the characteristics and needs of students. This study aims to evaluate the use of digital media in PAI learning through a literature study approach. The research method used is a literature study by reviewing five national journal articles relevant to the research topic. Data were analyzed using a qualitative descriptive approach to identify the forms of digital media utilization, the benefits obtained, and the obstacles encountered in its implementation. The study results show that digital media, such as instructional videos, audio-visual media, learning applications, and e-learning platforms, positively contribute to increasing learning motivation, material understanding, and student engagement in Islamic Religious Education (PAI) learning. However, the effectiveness of digital media utilization is still influenced by teachers' digital competence, the availability of facilities and infrastructure, and the media's suitability to the objectives and characteristics of Islamic Religious Education (PAI) learning. Therefore, ongoing and planned evaluation is necessary to ensure optimal digital media utilization and support the achievement of Islamic education goals.